Entorno familiar y rendimiento académico en estudiantes del nivel secundaria de la I.E.P.S.M. N⁰ 60279 San Juan Camucheros distrito de San Pablo 2024 - Da Costa Perez, Nery (2025)
The purpose of this research was to determine how the family environment relates to academic performance in secondary school students at I.E.P.S.M. No. 60279 San Juan de Camucheros, district of San Pablo 2024. The study was basic and had a non-experimental cross-sectional design. The sample consisted of the entire population, which was 60 secondary school students. In the results, in the Family Environment variable, 41.7% of students perceive it as average, 33.3% consider it good, and 25.0% consider it poor. Regarding the academic performance variable, 43.3% of students achieve average performance, 35.0% show poor performance, and only 21.7% are at the good level. Likewise, Spearman's Rho test shows a positive and significant correlation between family environment and academic performance (r=0.534; p=0.002). This allows us to reject the null hypothesis and accept the alternative, concluding that there is a significant relationship between the variables.